La cultura y la motivación en una empresa de tecnología - Florez Espinosa, Johanna (Universidad Antonio Nariño, 2022)
The present is a qualitative, inductive and correlational research work, its objective is to determine the influence of the organizational culture on the motivation of the workers of the technology company Cafetosoftware. This research is considered important since currently the technology market executes innovative processes to boost organizational performance. Therefore, the established study seeks to delve into new forms of interpretation and identification of existing factors between culture and motivation, seen from the operation of a technology company.